Sulfidic mine tailings and marl waste rock as compatible resources in a microwave-assisted roasting process. (20th November 2020) - Everaert, Maarten; Lemmens, Vincent; Atia, Thomas Abo; Spooren, Jeroen
Abstract: Copper (Cu) is a popular commodity metal, and novel technologies are being developed to extract Cu from low-grade sources, such as sulfidic tailings. Roasting of tailings allows efficient Cu extraction and reduces environmental risks associated with tailing storage. However, conventional roasting is energy-intensive and releases harmful sulfur oxide gas (SOx ). This study combines two mining wastes, sulfidic tailing and carbonate-rich waste rock (marl), in an energy-efficient microwave-assisted roasting step to simultaneously oxidize sulfide minerals and fixate formed SOx gas as sulfates. The roasting procedure was first optimized via conventional roasting (varying temperature, mixing ratio) by characterizing roasted materials (XRD/Rietveld, SEM-EDX, XRF, TGA-MS). Later, these optimized conditions were tested with microwave-assisted roasting. Subsequently, the influence of roasting treatments on Cu extraction was examined via ammoniacal leaching. Results showed that sulfate formation (SOx fixation) was highest for roasting at 500 °C via conventional roasting and increases with increasing marl content. Microwave-assisted roasting at 500 °C performs slightly below conventional roasting, as FeS2 was not fully oxidized. Marl addition negatively affects Cu extraction, likely because it limits the formation of water-soluble CuSO4 . This study demonstrates the potential of mixing marl with tailings to control SOx emissions during roasting, but also shows limitations in terms of Cu extraction. Graphical abstract: Image 1 Highlights: Tailing microwave roasting in presence of marl is proposed prior to Cu extraction. Sulfate formation (SOx fixation) during roasting increases with marl addition. Microwave-roasting at 500 °C performs slightly below conventional roasting. Marl addition limits formation of CuSO4 and negatively affects Cu extraction.